Antileishmanial, DNA Interaction, and Docking Studies of Some Ferrocene‐Based Heteroleptic Pentavalent Antimonials. Issue 1 (2nd December 2015) - Rauf, Muhammad Khawar; Shaheen, Ummara; Asghar, Faiza; Badshah, Amin; Nadhman, Akhtar; Azam, Sikander; Ali, Muhammad Irshad; Shahnaz, Gul; Yasinzai, Masoom
Abstract : A series of ferrocenyl pentavalent antimonials (1 –8 ) were synthesized and characterized by elemental analysis, FT‐IR, and multinuclear ( 1 H and 13 C) NMR spectroscopy. These antimonials were evaluated for their antileishmanial potential against Leishmania tropica KWH23, and by biocompatibility and membrane permeability assays. Moreover, mechanistic studies were carried out, mediated by DNA targeting followed by computational docking of ferrocenyl antimonials against the leishmanial trypanothione reductase enzyme. It was observed that the antimonials1 –8 were 390‐fold more efficacious (IC50 ) as compared with the standard antimonial drug used. Cytotoxicity results showed that these antimonials are highly active even at low concentrations and are biocompatible with human macrophages. Antimonials1 –8 exhibited extensive intercalation with DNA and, furthermore, docking interactions highlighted the potential interactive binding of the anitimonials within the trypanothione reductase active site, with van der Waals interactions contributing significantly to the process. Hence, it is suggested that the reported antimonials demonstrate high efficacy, less toxicity, and target multiple sites of the Leishmania parasite. Abstract : A series of ferrocenyl pentavalent antimonials were synthesized and evaluated for their antileishmanial potential, and by biocompatibility and membrane permeability assays. The antimonials1–8 were 390‐fold more efficacious (IC50 ) than the standard antimonial drug, with lower toxicity. Docking interactions showed interactive binding of the anitimonials within the trypanothione reductase active site.